1994
DOI: 10.1002/art.1780370617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of memory, learning ability, and clinical neurologic function in pathogen‐free mice with systemic lupus erythematosus

Abstract: Objective. To determine if neurologic impairment is related to progressive autoimmune disease in 3 murine models of systemic lupus erythematosus (SLE): MRLl lpr, NZB, and NZBIWF,.Methods. Sensorimotor function, learning, and memory were tested within strains at specific ages, before and after the appearance of SLE. These parameters were also compared between strains for young and older lupus mice and their congenic controls with reduced autoimmune disease (MRL/lpr versus MRL/+ ; NZB versus NZB/xid).Results. Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 28 publications
(30 reference statements)
2
32
0
Order By: Relevance
“…Similarly to lupus patients, MRL-lpr mice spontaneously develop behavioral dysfunction concerning emotional reactivity, motivated behavior, cognition, as well as pathologic changes in the brain (i.e. degeneration of central neurons) [62,[78][79][80][81][82][83][84][85][86][87]. Experimental studies showed that behavioral deficits parallel high levels of cytokines and autoAb, such as antinuclear Abs, anti-dsDNA, and RF, resulting in large amounts of immune complexes [71].…”
Section: The Mrl-lpr Mouse Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly to lupus patients, MRL-lpr mice spontaneously develop behavioral dysfunction concerning emotional reactivity, motivated behavior, cognition, as well as pathologic changes in the brain (i.e. degeneration of central neurons) [62,[78][79][80][81][82][83][84][85][86][87]. Experimental studies showed that behavioral deficits parallel high levels of cytokines and autoAb, such as antinuclear Abs, anti-dsDNA, and RF, resulting in large amounts of immune complexes [71].…”
Section: The Mrl-lpr Mouse Modelmentioning
confidence: 97%
“…Longer latencies indicate poorer performance. MRL-lpr mice present significant deficits in this test; they are dramatically impaired in their ability to learn the spatial relationships required to guide them to the hidden platform [80,81,86,112].…”
Section: Morris Water Mazementioning
confidence: 99%
“…Similar to SLE in humans, an inbred strain of MRL/MpJ-Fas lpr (MRL-lpr) mice develops an accelerated SLE-like condition (Theofilopoulos, 1992) accompanied by various neurological dysfunctions (Hess et al, 1993;Vogelweid et al, 1994), an anxious/depressive-like behavioral state (Sakic et al, 1994), ventricular enlargement (Denenberg et al, 1992), neuronal atrophy, and retarded brain growth (Sakic et al, 2000a;Sakic et al, 1998). Pathological abnormalities are also seen in the choroid plexus, a structure that synthesizes most of the cerebrospinal fluid (CSF) volume (Duprez et al, 2001;Schwartz and Roberts, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The TLRs trigger innate immunity; because TLR7 binds viral RNA, it may be viral RNA that exacerbates the autoimmune response. Furthermore, because pathogen-free mice also develop lupus (19), the RNA may be produced by endogenous retrovirus.…”
mentioning
confidence: 99%